CoTe nanoparticle-embedded N-doped hollow carbon polyhedron: an efficient catalyst for H2O2 electrosynthesis in acidic media. Issue 38 (22nd September 2021) - Zhang, Longcheng; Liang, Jie; Yue, Luchao; Dong, Kai; Xu, Zhaoquan; Li, Tingshuai; Liu, Qian; Luo, Yonglan; Liu, Yang; Gao, Shuyan; Asiri, Abdullah M.; Kong, Qingquan; et al.
Abstract : CoTe nanoparticles embedded nitrogen-doped hollow carbon polyhedron (CoTe@NC) acts as a highly efficient 2e − O2 reduction reaction electrocatalyst with a high selectivity of up to 92.6% at 0.3 V, significantly outperforming CoTe and NC counterparts. Abstract : Rational design and development of high-efficiency electrocatalytic materials made from earth-abundant elements for H2 O2 generation via a two-electron O2 reduction reaction (2e − ORR) is of crucial significance but still challenging. Here, we demonstrate that CoTe nanoparticles embedded in a nitrogen-doped hollow carbon polyhedron (CoTe@NC) can be adopted as a highly selective and stable 2e − ORR electrocatalyst. Benefiting from the synergistic effect between the highly active CoTe nanoparticles and nitrogen-doped hollow carbon polyhedron, in 0.1 M HClO4, the CoTe@NC hybrid exhibits superb electrocatalytic activity toward the 2e − ORR with high selectivity of up to 92.6% and a large H2 O2 production rate of 297.9 ppm h −1 at −0.044 V versus reversible hydrogen electrode. Moreover, it operates rather stably under the working conditions with a negligible current decrease after 12 h. Theoretical calculations further provide insight into the catalytic mechanism involved.